The UN Decade of Ocean Science for Sustainable Development - Ryabinin, Vladimir; Barbière, Julian; Haugan, Peter; Kullenberg, Gunnar; Smith, Neville; McLean, Craig; Troisi, Ariel; Fischer, Albert; Aricò, Salvatore; Aarup, Thorkild; Pissierssens, Peter; Visbeck, Martin; et al. (Frontiers in Marine Science, 2019)
Our civilization needs a clean, resilient, productive, safe, well-observed, documented and predicted ocean. “The ocean we need for the future we want” was the motto of the IOC proposal to the United Nations to consider the merit of an Ocean Science Decade. By proclaiming the Decade, the UN General Assembly offered the oceanographic community a unique, once in a life-time, opportunity to change the way we do things, make oceanography fit for purpose of effectively supporting sustainable development, and energize the ocean sciences for future generations. The Decade is the chance to put in place a more complete and sustainable observing system and feed the resulting data into a science-based informed decision-making system allowing increased reliance of our civilization on the ocean, its ecosystem services and, at the same time, preserving ocean health. Strong and proactive engagement of the oceanographic community in the design of the Decade and its observing component and subsequent energetic implementation of the ideas are sought. Participants in OceanObs’19 are invited to consider the additional possibilities and requirements associated with the Decade in their contributions to and brainstorming at the Conference. It is essential to use collective wisdom of OceanObs’19 to help developing an ambitious and also realistic implementation plan for the Decade, with a strong observational component.